Microtubules and pancreatic amylase release by mouse pancreas in vitro (The Rockefeller University Press, 1976)
The effects of vinblastine and colchicine on pancreatic acinar cells were studied by use of in vitro mouse pancreatic fragments. Vinblastine inhibited the release of amylase stimulated by bethanechol, caerulein, or ionophore A23187. Inhibition required preincubation with vinblastine,and maximum inhibition was observed after 90 min. Inhibition was relatively irreversible and could not be overcome by a high concentration of stimulant. Inhibition could also be produced by colchicine although longer preincubation was required and inhibition was only partial. Uptake of [3H]vinblastine and [3H]colchicine by pancreatic fragments was measured and found not to be responsible for the slow onset of inhibition by these drugs. In incubated pancreas, microtubules were present primarily in the apical pole of the cell and in association with the Golgi region. Vinblastine, under time and dose conditions that inhibited the release of stimulated amylase, also reduced the number of microtubules. The only other consistent structural effects of vinblastine were the presence of vinblastine- induced crystals and an increased incidence of autophagy. The remainder of cell structure was not affected nor were overall tissue ATP and electrolyte contents or the stimulant-induced increase in 45Ca++ efflux. It is concluded that the antisecretory effects of vinblastine and colchicine are consistent with a microtubular action, but that acinar cell microtubules are more resistant to the drugs than many other cell types.